DESIGN AND BUILD A MINI POWER BANK AS A STORAGE ELECTRIC ENERGY FROM DRAGONS FRUIT STEM (HYLOCEREUS POLYRHIZUS) (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2022)
Research has been carried out on the design of a mini power bank using dragon paste as a source of electrical energy. The voltage and current produced by this dragon paste and power bank are measured using a digital multimeter. Dragon paste used in series and parallel. The voltage generated by the dragon paste is connected to a DC step up. The use of step up dc aims to increase the dragon paste voltage, so that the resulting voltage can reach a maximum of 5.16 V and can charge lithium-ion batteries that have been arranged in parallel using the power bank kit module.